2001
DOI: 10.4049/jimmunol.167.8.4450
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution and Stability of Epitope-Specific CD8+ T Cell Responses in EBV Infection

Abstract: Murine models of lymphocytic choriomeningitis virus infection suggest that the memory CD8+ T cell repertoire is reflective of the CD8+ T cell repertoire generated during acute infection. Less is known regarding the evolution of CD8+ T cell repertoires during human viral infections. We therefore examined epitope-specific CD8+ T cell responses in a large cohort of individuals with acute through latent Epstein-Barr virus infection. Using 16 of 20 published EBV epitopes restricted by HLA-A2, HLA-A3 or HLA-B7, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 38 publications
5
92
2
Order By: Relevance
“…ELISPOT assay and tetramer staining identify virus-specific CD8 ϩ T cells directly ex vivo and therefore may more accurately reflect CD8 ϩ T cell specificities in vivo. Finally, the protein specificity of HCMV-specific CD8 ϩ T cell responses may depend on HLA type (52,60,61). In our study all infants with responses to pp65 alone were HLA-A2 ϩ , whereas only one-third of those with responses to both gene products were HLA-A2 ϩ .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…ELISPOT assay and tetramer staining identify virus-specific CD8 ϩ T cells directly ex vivo and therefore may more accurately reflect CD8 ϩ T cell specificities in vivo. Finally, the protein specificity of HCMV-specific CD8 ϩ T cell responses may depend on HLA type (52,60,61). In our study all infants with responses to pp65 alone were HLA-A2 ϩ , whereas only one-third of those with responses to both gene products were HLA-A2 ϩ .…”
Section: Discussionmentioning
confidence: 55%
“…We and others have previously shown phenotypic and functional heterogeneity of virus-specific CD8 ϩ T cell populations over the course of viral infections (52,54). Tetramer staining is a method that quantifies epitope-specific T cells without regard to functional activity; thus, virus-specific T cell frequencies detected by tetramer staining are commonly higher than those detected by other methods.…”
Section: Comparison Of Tetramer Staining and Elispot Assaysmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it seems that the determination of IE-and pp65-specific CD8 + T cells may in some cases underestimate the real efficiency of the immune system against HCMV infection. In this respect, it seems important to recall that changes in the protein and epitope specificity of HCMVspecific CD8 + T cells over time have been reported in children with congenital or postnatal HCMV infection [18] as well as during Epstein-Barr virus infection [19]. This might be due to different viral antigen processing and presentation [20].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, whereas similar high frequencies of T cells reactive to the BMLF-1 (GLC) epitope were obtained using IFN-DCs or IL-4-DCs as stimulators, the expansion of T cells specific for the gp350 epitope was promoted exclusively by IFNDCs. Several studies have demonstrated that responses to lytic cycle Ags, including BMLF-1, are detectable in CTL memory (21,30,31) and can dominate those to latent cycle Ags (32), as in the case of donor LL, whose basal frequency of T cells reactive against the BMLF-1 (GLC) epitope largely exceeded that of each latent cycle Ag reactivity tested. Moreover, BMLF-1 (GLC) epitope-specific T cells can be easily detected in sensitive ELISPOT assays by adding the corresponding peptide to total PBMCs as responders (30,32), indicating that relatively inefficient APCs, such as the IL-4-DCs used in this study, can stimulate T cells reactive to this immunodominant epitope.…”
Section: Discussionmentioning
confidence: 99%